Implementasi Aplikasi Sistem Informasi Manajemen Badan Permusyawaratan Desa (SIM BPD) dalam Penyampaian Informasi dan Penyerapan Aspirasi Masyarakat di Desa Punggul, Kecamatan Abiansemal Kabupaten Badung - I Made Yudi Dwipayana; I Made Yudhiantara; Toto Noerasto (Public Inspiration : Jurnal Administrasi Publik, 2023)
Villages as the lowest government entity have implemented an information technology-based village concept known as Smart Village. Punggul Village, Abiansemal District, Badung Regency is one of the villages that actively uses technology systems in all government activities and community service activities. One of the application innovations owned by Punggul Village is the BPD SIM application. This research seeks to analyze the implementation of the BPD SIM application. The aim of the research is to analyze and describe the implementation of the BPD SIM application in Punggul Village and determine the factors inhibiting the implementation of the BPD SIM in Punggul Village. The research approach uses a qualitative descriptive method with the application of Edward III's theory. Data collection was carried out using observation techniques, in-depth interviews and documentation. The selection of informants used purposive sampling techniques, and qualitative data analysis was inductive. The research results show that the implementation of the BPD SIM application in Punggul Village has not been effective based on the perspective of communication, resources, disposition and bureaucratic structure. Factors inhibiting implementation are socialization that has not run optimally, inadequate resources, not having the same understanding between BPD officials, and a lack of clear division of tasks in implementing this application.